Cartografia: uma introdução aos conceitos de geometria não euclidiana na educação básica - Mülhbauer, Marlon (2014)
This project propose the introduction to non Euclidean geometries, especially Spherical Geometry in high school for second graders in order to improve the processes of teaching and learning that discipline. Includes a brief history of geometry, with names like Euclides, Bolyai, Lobachevsky and Riemann, and its importance to the improvement of this content. Furthermore, cartography topics were explained to level the knowledge and can achieve an important result: the determination of the distance between two points on the surface of a sphere. The activities implemented for students appearing in the appendix, after all the explanation of the classes and worked contents.